2018
DOI: 10.1016/j.toxrep.2017.12.016
|View full text |Cite
|
Sign up to set email alerts
|

New research highlights: Impact of chronic ingestion of white kidney beans (Phaseolus vulgaris L. var. Beldia) on small-intestinal disaccharidase activity in Wistar rats

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Dietary provocative agents such as Phytohemagglutinin (PHA), a red kidney bean lectin, and microbial protease (PT), found in dairy products such as cheese, cause precocious gut maturation characterized by a decrease in macromolecule absorptive capacity, an increase in intestinal length and acceleration of epithelial cell growth, an effect which is independent of gut bacteria . The current study by Marungruang et al .…”
Section: Gut Microbiota and The Gastrointestinal Barriermentioning
confidence: 96%
See 1 more Smart Citation
“…Dietary provocative agents such as Phytohemagglutinin (PHA), a red kidney bean lectin, and microbial protease (PT), found in dairy products such as cheese, cause precocious gut maturation characterized by a decrease in macromolecule absorptive capacity, an increase in intestinal length and acceleration of epithelial cell growth, an effect which is independent of gut bacteria . The current study by Marungruang et al .…”
Section: Gut Microbiota and The Gastrointestinal Barriermentioning
confidence: 96%
“…The maturation of the GIB depends on diet and the gut microbiota in addition to other factors (reviewed in). Dietary factors can promote the maturation of the GIB both in a microbiota dependent and independent manner . Diet has a significant effect on gut microbiota composition and function; hence, it is not surprising that post‐weaning there is an overall increase in microbial diversity (transient decrease in microbial diversity shortly after weaning followed by increase in microbial diversity over a long‐term), which in turn coincides with maturation of the GIB.…”
Section: Gut Microbiota and The Gastrointestinal Barriermentioning
confidence: 99%
“…In all cases, beans were either consumed raw, soaked, or cooked using temperatures inadequate to destroy PHA. Nonetheless, PHA toxin appears to be eliminated by 10 min of boiling [ 29 ]. Mechanistically, lectins and hemagglutinins are resistant to digestion by both host enzymes and bacteria, and therefore pass through the gastrointestinal tract functionally and immunologically intact.…”
Section: Lectinsmentioning
confidence: 99%
“…This change in intestinal integrity resulted in compromised nutrient absorption (protein, lipid and vitamin B12) and reduced growth of experimental animals [ 34 , 35 , 36 , 37 ]. Nciri and colleagues demonstrated that administration of 300 mg of a raw Beldia bean (white kidney bean) flour for 10 days caused intestinal alterations, distorted jejunum morphology of the microvilli, and reduced enzyme activity in mice [ 29 , 38 ]. Another proposed mechanism of PHA toxicity is intestinal dysbiosis secondary to PHA-induced intestinal damage [ 37 , 39 ].…”
Section: Lectinsmentioning
confidence: 99%
“…Although some digestive enzymes would not affect the α-AI, the pH of the hydrolysis will inevitably cause adverse influences on the α-AI activity [18]. The α-AI tends to retain its activity in the condition with pH between 3 and 7, which is suitable for some commercial proteases [16].…”
Section: Introductionmentioning
confidence: 99%